Demystifying the fusion mechanism in heavy-ion collisions: A six-dimensional Langevin dissipative dynamics approach - Y. Jaganathen; M. Kowal; K. Pomorski (Physics Letters B)
We present an in-depth investigation of heavy-ion fusion dynamics using a six-dimensional Langevin framework that enables unrestricted motion of the asymmetry parameter. The stochastic formalism naturally incorporates friction effects and energy fluctuations, providing a detailed understanding of the fusion process. The dynamics transition into the overdamped regime, facilitating rapid neck stabilization while effectively capturing the interplay between shape and rotational degrees of freedom. This approach achieves excellent agreement with experimental spin distributions and fusion cross-sections, establishing a robust foundation for forthcoming studies on the synthesis of superheavy elements and the exploration of the enigmatic fusion hindrance mechanism.